Structural studies on MRG701 chromodomain reveal a novel dimerization interface of MRG proteins in green plants. Issue 11 (8th September 2016) - Liu, Yanchao; Wu, Hong; Yu, Yu; Huang, Ying
Abstract: MRG proteins are conserved during evolution in fungi, flies, mammals and plants, and they can exhibit diversified functions. The animal MRGs were found to form various complexes to activate gene expression. Plant MRG1/2 and MRG702 were reported to be involved in the regulation of flowering time via binding to H3K36me3-marked flowering genes. Herein, we determined the crystal structure of MRG701 chromodomain (MRG701 CD ). MRG701 CD forms a novel dimerization fold both in crystal and in solution. Moreover, we found that the dimerization of MRG chromodomains is conserved in green plants. Our findings may provide new insights into the mechanism of MRGs in regulation of gene expression in green plants.